2015
DOI: 10.5430/jnep.v5n8p121
|View full text |Cite
|
Sign up to set email alerts
|

Social desirability bias in relation to academic cheating behaviors of nursing students

Abstract: The purpose of this study was to explore the relationship between academic cheating and a series of academic and demographic characteristics, as well as the relationship between the various characteristics and social desirability bias. The population for the study was comprised of 626 nursing students (pre-nursing, baccalaureate students formally admitted into the program, and graduate students) attending a regional comprehensive university located in the Midwest. The results of the study revealed that 53.8% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 41 publications
(61 reference statements)
3
25
3
Order By: Relevance
“…Deliberate cheating was negatively correlated with age and semester credits completed, implying that younger students are more likely to engage in this form (Winrow et al . ).…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Deliberate cheating was negatively correlated with age and semester credits completed, implying that younger students are more likely to engage in this form (Winrow et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, another study involving 626 participants also found a positive correlation (Spearman's rank correlation coefficient 0·473; p < 0·05) between plagiarism and professional misconduct (Winrow et al . ). Balik et al .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations